Discovery of essential kinetoplastid-insect adhesion proteins and their function in Leishmania -sand fly interactions - Yanase, R; Pruzinova, K; Owino, BO; Rea, E; Moreira-Leite, F; Taniguchi, A; Nonaka, S; Sádlová, J; Vojtkova, B; Volf, P; Sunter, JD (Nature Research, 2024)
Leishmania species, members of the kinetoplastid parasites, cause leishmaniasis, a neglected tropical disease, in millions of people worldwide. Leishmania has a complex life cycle with multiple developmental forms, as it cycles between a sand fly vector and a mammalian host; understanding their life cycle is critical to understanding disease spread. One of the key life cycle stages is the haptomonad form, which attaches to insect tissues through its flagellum. This adhesion, conserved across kinetoplastid parasites, is implicated in having an important function within their life cycles and hence in disease transmission. Here, we discover the kinetoplastid-insect adhesion proteins (KIAPs), which localise in the attached Leishmania flagellum. Deletion of these KIAPs impairs cell adhesion in vitro and prevents Leishmania from colonising the stomodeal valve in the sand fly, without affecting cell growth. Additionally, loss of parasite adhesion in the sand fly results in reduced physiological changes to the fly, with no observable damage of the stomodeal valve and reduced midgut swelling. These results provide important insights into a comprehensive understanding of the Leishmania life cycle, which will be critical for developing transmission-blocking strategies.